Europe in an Age of Austerity - Borooah, Vani K.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This study discusses and analyses the broad issues that have underpinned the current European economic crisis. It examines the experiences of three countries - Greece, Ireland, and Portugal - which reveal an economic system which lacks the adjustment mechanisms that countries with sovereign currencies take for granted.
Keywords: Science